mrs rosa said:
i really need help with this problem : 2/3 (p-6) +4=1/6
You have the equivalent of
\(\displaystyle \frac{2}{3}(p - 6) + 4 = \frac{1}{6}\)
I recommend that you clear denominators at the outset. That way, in this certain problem, you will just work
with integer coefficients and integer constants until the end portion of solving for the variable.
The least common denominator, which is the least common multiple of the denominators \(\displaystyle 3 \\) and \(\displaystyle \ 6, \\) is \(\displaystyle \ 6.\)
Multiply each term on both sides by \(\displaystyle 6,\) or by the equivalent form \(\displaystyle \frac{6}{1}\), to clear denominators.
\(\displaystyle \frac{6}{1}[\frac{2}{3}(p - 6)] + 6(4) = \frac{6}{1}(\frac{1}{6})\)
\(\displaystyle 4(p - 6) + 24 = 1\)
\(\displaystyle 4p - 24 + 24 = 1\)
\(\displaystyle 4p = 1\)
\(\displaystyle \frac{4p}{4} = \frac{1}{4}\)
\(\displaystyle \boxed{p = \frac{1}{4}}\)